Fast Overcurrent Protection for Direct Drive Cascode GaN HEMT Semiconductors Based on Industrial Gate Drivers - Vico, Enrico; Stella, Fausto; Giuffrida, Simone; Bojoi, Radu (Conference proceedings - IEEE Applied Power Electronics Conference and Exposition, 2024)
Gallium nitride high electron mobility transistors exhibit excellent switching and conduction performance. However, their adoption in safety-critical applications is subject to concerns about their capability to withstand severe overcurrents. Therefore, fast and reliable overcurrent protections are needed to guarantee the safe operation of the power switches. The conventional desaturation protection methods, widely used for MOSFETs and IGBTs, do not match with the reduced short-circuit capability of new GaN HEMTs semiconductors. To address this issue, this paper proposes a fast overcurrent protection scheme specifically designed for direct drive cascode GaN HEMT. The proposed solution uses an industrial gate driver along with a few additional components, leveraging the measurement of the conduction voltage of the cascode MOSFET as an indirect indicator of the device current with very good precision and reduced intervention time. The effectiveness of the proposed overcurrent protection scheme is supported by experimental results.